The Influence of Clarity Budget Targets, Budget Accuracy on Performance Accountability of Government Agency Through the Internal Control System as an Intervening Variable - Sri Karnila; Tenriwaru Tenriwaru; Baso Amang (Faculty of Economics dan Business, Atma Jaya Makassar University, 2024)
This research was conducted with the aim of analyzing how much influence clarity of budget targets, budget accuracy has on the accountability of government agency performance through the internal control system as an intervening variable in the public works department and spatial planning of West Sulawesi province. This research uses a quantitative type of research with a descriptive analysis approach. The population in this study was 141 employees at the Department of Public Works and Spatial Planning in West Sulawesi province. The respondents used were employees in charge of preparing financial reports for each field so that the sample in this study was 45 respondents. The data collection technique used was a questionnaire using a Likert scale. The data analysis technique used in this research uses the Structure Equation Model (SEM) method based on Partial Least Square (PLS). The results of this research show: clarity of budget targets, budget accuracy and internal control systems influence the accountability of government agency performance. clarity of budget targets, budget accuracy affects the internal control system. Internal control as an interverning variable can influence the clarity of budget targets and budget accuracy on performance accountability